Prevalence of transthyretin amyloid cardiomyopathy in male patients who underwent bilateral carpal tunnel surgery: The ACTUAL study. (15th April 2021) - Vianello, Pier Filippo; La Malfa, Giovanni; Tini, Giacomo; Mazzola, Vittoria; Miceli, Alberto; Santolini, Emmanuele; Briano, Stefania; Porto, Italo; Canepa, Marco
Abstract: Introduction: Bilateral carpal tunnel syndrome (CTS), particularly in male individuals with left ventricular hypertrophy (LVH), has been recognized as a red flag for transthyretin cardiac amyloidosis (TTR-CA). Nonetheless, the opportunity of screening CTS patients for TTR has yet to be determined. Methods: Medical records of 1689 CTS surgeries performed at our institution between 2008 and 2018 were reviewed. Eighty-three males who underwent bilateral CTS surgery were considered eligible for the study, and offered a screening examination including electrocardiography and echocardiography. Individuals with LVH (diastolic septal wall thickness > 12 mm) were offered second-line diagnostic testing including blood testing and bone scintigraphy. Results: Study population consisted of 53 bilateral CTS male patients, with median age of 73 years. LVH was found in 6 (11%) individuals. None of them had monoclonal gammopathy or reported CTS occupational risk factors. Two declined to undergo further testing, whereas 2 had negative and 2 had positive bone scintigraphy (both Perugini 2 uptake) and tested negative for TTR gene mutations (wild-type TTR-CA). Conclusions: Prevalence of TTR-CA in the entire study population was 4%, but among bilateral CTS patients with LVH peaked at 33%. In this latter population, screening for TTR-CA appeared feasible and effective. Highlights: Bilateral carpal tunnel syndrome (CTS), in particular in males, is a red flag suggesting a diagnosis of transthyretin cardiac amyloidosis (TTR-CA). We investigated the presence of TTR-CA in male individuals who had undergone bilater CTS surgery. Prevalence of TTR-CA in the entire study population was 4%, but among bilateral CTS patients with left ventricular hypertrophy peaked at 33%.